Phenomenon Traditional Gold Mining In Lebong Tambang Village, District Lebong - Aulian, Anggis; Suminar, Panji; Widiyarti, Diyas (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study examines the phenomenon of traditional gold mining in Lebong Tambang Village, Lebong District. This activity has been prevalent since the Dutch colonial era. To this day, local residents consider it their only option to meet their economic needs. This study aims to understand how the community interprets gold mining practices in their daily lives and to identify the factors that drive community involvement in this activity. This study uses a qualitative descriptive method with data collection instruments in the form of observation, in-depth interviews, and documentation. The theory used is Alfred Schutz's phenomenological theory, which explains that community involvement in gold mining is influenced by causal motives, past experiences, inherited traditions, and family socioeconomic conditions that shape the view that mining is a natural and inherited occupation. Mining is also driven by the desire to fulfill life's needs (earn income), maintain family economic sustainability, and the community's lifeworld. This activity is considered a routine, social essence, and collective meaning that is naturally accepted in everyday life. Thus, mining is not merely an economic activity, but has become part of the social identity and traditions of the Lebong Tambang Village community.